The Existence of Islamic Education Responds to the Challenges of Changing the World of Education in the Era of the Industrial Revolution 4.0 - Rahayu, Windi; Amelia, Rizki; Saputra, Ramadhan; Sukatin; Aprianto, Iwan (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Education in a theoretical philosophical definition is human thought on educational problems solving and compiling new theories by based on normative, speculative, empirical rational, philosophical, and historical philosophical thinking. While rducation in the definition of practice is an optimal transfer or transformation of knowledge or development, as well as cultivating human beings in the transformation of key values. The purpose of Islamic education is to make students more wary of Allah SWT. The Industrial Revolution era 4.0 was an integration of technology and human to make work done easier. The problem of Islamic education is that the basic problem of education in Indonesia is the low quality of education. This is demonstrated by the large differences in the quality of education between regions. The State-level educational development index shows two trends. Islamic education needs to change, which is to change old ideas that are outdated and related to bureaucratic rules, to self-development and innovation cooperatives in an aspect of the world: to change the method of prioritizing education that fits modernity, especially in islamic education, which is embedded in the ancestral values of the nation and religion.